Blast Eye Injury After Mobile Phone Battery Explosion: How to Manage it? - Ratih Justitia Kartika; Ismi Zuhria (Vision Science and Eye Health Journal, 2022)
Introduction: Injuries from mobile phone blasts have been on the rise in recent years. Lithium-ion batteries are the most common type found in cellphones and devices. In 2016 around 100 of the 2.5 million phone cell units have been recorded to have exploded. Mobile battery burst is a significantly underappreciated cause of serious ocular morbidity and could be a combination of mechanical, thermal, and chemical effects. Knowing proper management is very important to achieve the best result. Case presentation: We describe an ocular blast injury due to mobile phone battery explosion when plugged in to charge that experienced spasm and burned cilia, limbal ischemia, broad corneal haziness on both eyes, and visual acuity decreased. The fluorescein test was positive. We did proper irrigation and debris extraction around the ocular surface and periorbital tissue. It was treated with quinolone antibiotics eyedrop, atropine sulfate eyedrop, prednisolone eyedrop, and NSAID orally. In four days, the patient’s eye showed good clinical improvement with decreased corneal haziness with minimal epithelial defect. The visual acuity was improved on both eyes. Conclusions: Lithium-ion batteries are used in almost all smartphones and electronics. Lithium explosions can result in chemical and thermal burns on the ocular surface. Ocular alkali chemical injury combined with thermal and mechanical is an emergency case. The vision can be saved if the ocular surface burns are treated promptly and properly. These cases are required to raise public awareness about the potential risks of smartphone use, adopt safe practices as recommendations from the manufacturers, and avoid counterfeit products and such accidents.